Study of Postdatism with Respect to Fetomaternal Outcome at A Tertiary Care Hospital - Sadaf, Rabeea; Shamsher, Sadia; Tabassum, Shazia; Kishwar, Nasreen; Rauf, Bushra; Parveen, Zahida (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study aims to know our setup’s fetomaternal pregnancy complications that extend beyond 40 weeks of gestation. METHODOLOGY This is a prospective cross-sectional study of 390 patients with uncomplicated postdated pregnancies fulfilling the inclusion and exclusion criteria admitted to the department of Obstetrics and Gynecology (both in spontaneous labour and induced patient) at Hayatabad Medical Complex, a tertiary care hospital in Peshawar, KPK from July 2020 to June 2021. RESULTS Out of 390 patients, a majority (72.30 %) were in the age group of 20 – 35 years. Most of them (50.51%) presented at gestation 40+1 – 40+6 weeks. The majority (57.69%) were multigravida, and most (93.07%) were un-booked. Most delivered vaginally (80.51%), and 19.48% had C/section (including both emergency and elective). The most common indication for C/section was fetal distress (44.73%), followed by C/section on demand (18.42%). The majority>90% had Apgar score greater than seven at 5 minutes which was gestation dependent. Overall perinatal mortality was 4.07% which was also gestation dependent ranging from 0.5% at 40+1 – 40+6 weeks to 2.30% at and beyond 42 weeks of gestation. Neonatal morbidity in the form of Birth asphyxia, Meconium Aspiration Syndrome (MAS), Shoulder Dystocia and NICU admission also showed an increasing tendency with increasing gestation beyond 40 weeks. Maternal morbidity in the form of PPH, perineal tears 3°/4° and endometritis also showed a similar increasing trend with increasing gestation beyond 40 weeks. CONCLUSION Pregnancy continuing beyond 40 weeks has a definite risk to the fetus.